[Report of] the Committee appointed ... to examine the present condition of the Narragansett tribe of Indians and all the laws and acts of Assembly relating to them .
January 11, 1831 Committee report following a review of the Narragansett Indian tribal laws, including past history of the tribe. Following a rather disparaging assessment of the tribe and its current council, as well as indicating that most members were of mixed races, the author of said report, Dan King, and committee proposed numerous changes. Included were suggestions that the current laws be abolished and an overseer appointed for general oversight of the tribe and guardian of those who were "not competent"; and common lands be sold, with interest used to support the poor, pay down debts, and pay overseer. Of note, the committee anticipated the end of the tribe's existence and suggested the lands then be sold for the benefit of the nearby towns.